Soccercoaching
Collection of exercises: Possession Themes Passing - 16 Receiving - 1 Dribbling - 5 Heading - 14 Shooting - 9 Basic Skills - 1 1 versus 1 - 11 Building Up (From the Back) - 4 Feeding Forwards - 3 Attacking down the Wings - 5 Combinations - 17 Cooperation between the lines - 1 Finishing the Attack - 6 Movement off the Ball - 2 Switch Play - 1 Conditioning - 3 Coaching between players - 1 Counter Attacking - 1 Second Ball - 1 Field Positioning - 1